PENGARUH PENGGUNAAN SUPERPLASTICIZER NAFTALENA SULFONAT FORMALDEHIDA DAN POLIKARBOKSILAT ETER TERHADAP NILAI KUAT TEKAN BETON - , MARTINO ARDIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Public demand on concrete for construction materials is increasingly rising. The cost involved is not cheap to make concrete with high compressive strength. One way that can be used with the addition of chemicals. In this experiment used admixture materials, namely Naphthalene Sulfonate Formaldehyde (NSF) and polycarboxylic Ether (PCE), which serves as a superplasticizer with water reduction, thus increasing the compressive strength of concrete. In this experiment the chemical variation was 0.5%